LABOR UBERIZATION: NAVIGATING FROM INSTABILITY TO OPPORTUNITIES INTHE DIGITAL ERA (International Seven Journal of Multidisciplinary, 2025)
We investigated online job markets through a literature review and qualitative content analysis, using a diverse set of studies on uberization as a basis. Our objective was to analyze and systematize the characteristics of work on platforms, answering specific questions: Which areas of knowledge are exploring the uberization process? What are the main professional activities involved? What are the main impacts generated? The research was conducted on the Capes Periodicals Portal, through the Index (Web of Science), covering national and international articles published from January 2019 to October 2023. The results indicate that uberization is a topic of discussion in several areas of knowledge, with an emphasis on the areas of economics and sociology. In the economic context, various terminologies are used, such as "sharing economy", "collaborative economy", "collaborative consumption", "peer-to-peer economy", "on-demand economy" and "gig economy". This online model is impacting various economic sectors, stimulating investments and reconfiguring competitiveness. In the sociological sphere, linked to the human sciences, the analysis addresses the historical evolution of neoliberalism, culminating in the era of industry 4.0 and the uberization of work. Concepts such as precariousness, dignity, evolution of work, future of work, flexibility and exploitation of workers. Uberization is spreading across several professional categories, including app drivers, education professionals, police officers, doctors, lawyers, recruiters and coaches, presenting both positive and negative impacts of digital platforms. We conclude that urgent regulation of online services, app delivery drivers and other professions is necessary to guarantee labor rights, workplace safety and decent conditions. Technological advances, in turn, prove to be exclusionary for the majority of low-income young people, highlighting the urgency of public policies for digital inclusion starting in basic education. New working conditions will require the acquisition of professional skills aligned with new technologies, while updated regulations will be essential to ensure investments, job creation and protected work opportunities.